2021
DOI: 10.1016/j.ekir.2021.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation in Chronic Kidney Disease Progression: Role of Nrf2

Abstract: Despite recent advances in the management of chronic kidney disease (CKD), morbidity and mortality rates in these patients remain high. Although pressure-mediated injury is a well-recognized mechanism of disease progression in CKD, emerging data indicate that an intermediate phenotype involving chronic inflammation, oxidative stress, hypoxia, senescence, and mitochondrial dysfunction plays a key role in the etiology, progression, and pathophysiology of CKD. A variety of factors promote chronic inflammation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 159 publications
2
117
0
1
Order By: Relevance
“…In the last decade, several studies suggested that disruption of the Nrf2 signaling pathway was involved in several kidney diseases [ 74 , 75 , 76 ]. Nrf2 is a crucial transcription factor that plays a pivotal role in inducing the expression of cellular defense enzymes to counteract oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several studies suggested that disruption of the Nrf2 signaling pathway was involved in several kidney diseases [ 74 , 75 , 76 ]. Nrf2 is a crucial transcription factor that plays a pivotal role in inducing the expression of cellular defense enzymes to counteract oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a key component of several age-related pathologies, including CVDs and acute CKD, and the role of different pro-oxidant molecules, as well as the therapeutic effects of several antioxidants, have been widely studied both in experimental models and in clinical trials [ 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ].…”
Section: Cardiovascular Diseases As the Paradigm Of Age-related Chronic Diseases: Cardiorenal Syndromementioning
confidence: 99%
“…The reduced levels of AMPK contribute to an increase in Keap-1-Nrf-2 complex and a reduction in binding of Nrf-2 to the antioxidant response element and transcription of antioxidant enzymes, including heme oxygenase-1 (HO-1), super oxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) [ 46 ]. In addition, the inflammatory milieu related to CKD leads to reduced Nrf-2 transcriptional activity and renal antioxidant capacity [ 47 ].…”
Section: Signaling Pathways That Predispose To the Progression Of Ckdmentioning
confidence: 99%